Reducing Postpartum Anxiety in IUD Users through Ylang-ylang Aromatherapy and Slow Deep Breathing: A Quasi-Experimental Study - Luh Putu Widiastini; I Gusti Agung Manik Karuniadi; Gede Susila Dewi, Luh (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The number of IUD contraceptive users has declined, influenced by factors such as anxiety. Individuals with anxiety experience psychological distress, necessitating complementary therapy. Alternative treatments include ylang-ylang aromatherapy and Slow Deep Breathing. This study aimed to determine the effectiveness of ylang-ylang aromatherapy and Slow Deep Breathing in reducing anxiety among post-placental IUD users at Mangusada Hospital. Methods: A quasi-experimental nonequivalent control group design was used, involving 70 postpartum IUD users divided into experimental (n=35) and control (n=35) groups. Anxiety was measured using the NRS-A questionnaire before and after a 15-minute intervention. Ethical approval was obtained (070/6854/RSDM/2024). Data were analyzed using descriptive statistics, Kolmogorov-Smirnov for normality, Wilcoxon Signed-Rank, and Mann–Whitney U tests, with a 95% confidence level. Results: There was no significant difference in pre-test anxiety between the groups (mean: 5.69 ± 0.900, p = 1.000). Post-test results showed a greater reduction in the treatment group (mean: 3.03 ± 0.664) than in the control group (mean: 3.83 ± 0.785). The Mann-Whitney U test confirmed a significant difference in anxiety levels post-intervention (Z = -3.998, p = 0.000). The effect size (r = 0.676) indicates a large impact of the intervention. Conclusion: Ylang-ylang aromatherapy and slow deep breathing are effective complementary interventions for reducing anxiety in post-placental IUD users.